2008
DOI: 10.1007/s10194-008-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging in episodic cluster headache

Abstract: We have investigated the cerebral activation centre in four patients with episodic cluster headache (CH) with functional magnetic resonance imaging (f-MRI). The patients underwent MRI scans for anatomical and functional data acquisition in the asymptomatic state, during a headache attack and after subcutaneous administration of sumatriptan. Anatomical images were acquired by means of 3D-MPRAGE sequences and f-MRI images were obtained by means of echo-planar imaging. Data was analysed using the BrainVoyager QX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 10 publications
7
80
0
Order By: Relevance
“…Neuroimaging has suggested an abnormal or dysfunctional posterior hypothalamus as being central (12)(13)(14)(15). Clinical observations regarding the circadian and circannual symptomatology also point to pathology in the hypothalamus, especially the suprachiasmatic nucleus (SCN) (16,17).…”
Section: Pathophysiology Of Chmentioning
confidence: 99%
“…Neuroimaging has suggested an abnormal or dysfunctional posterior hypothalamus as being central (12)(13)(14)(15). Clinical observations regarding the circadian and circannual symptomatology also point to pathology in the hypothalamus, especially the suprachiasmatic nucleus (SCN) (16,17).…”
Section: Pathophysiology Of Chmentioning
confidence: 99%
“…Interestingly, these structural changes, which correlated with the pain duration, age-at-onset, pain intensity, and cortical activity were frequently co-localized and correlated with functional allodynic SI and SII activations documented by fMRI, and they may be speciWc targets for evaluating therapeutic interventions (DaSilva et al 2008). Finally, investigation of the cerebral activation in cluster headache before, during and after an attack, showed signiWcant hypothalamic activation of the hypothalamus ipsilateral to the pain side (DaSilva et al 2007;Morelli et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Several functional neuroimaging studies have been performed to investigate cortical function in patients suVering from orofacial pain, including positron emission tomography (PET) (Derbyshire et al 1994;Hagelberg et al 2003;Kupers et al 2000Kupers et al , 2004 and functional magnetic resonance imaging (fMRI) Blatow et al 2009;Borsook et al 2003;DaSilva et al 2007DaSilva et al , 2008de Leeuw et al 2005de Leeuw et al , 2006Jantsch et al 2005;Jiang et al 2006;Morelli et al 2008;Nash et al 2007). It has been found that SI and SII participate in the perception of sensory features of pain, together with other cortical areas (Apkarian et al 2005;Bushnell et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Functional and structural studies on cluster headache found activation and gray matter changes in the contralateral side of the pain [140][141][142][143]. Similar lateralisation of the white matter microstructural alterations were found in our investigation.…”
Section: Cluster Headachesupporting
confidence: 90%